1997
DOI: 10.1021/bi970540h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Nucleoside Triphosphate Cleavage and Phosphate Release Steps by Associated Rabbit Skeletal Actomyosin, Measured Using a Novel Fluorescent Probe for Phosphate

Abstract: We have measured the kinetics of inorganic phosphate (Pi) release during a single turnover of actomyosin nucleoside triphosphate (NTP) hydrolysis using a double-mixing stopped-flow spectrofluorometer, at very low ionic strength to increase the affinity of myosin-ATP and myosin-ADP-Pi to actin. Myosin subfragment 1 and a series of nucleoside triphosphates were mixed and incubated for approximately 1-10 s to allow NTP to bind to myosin and generate a steady state mixture of myosin-NTP and myosin-NDP-Pi. The stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
215
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(246 citation statements)
references
References 34 publications
26
215
5
Order By: Relevance
“…DOUBTS ABOUT SCHEME 1 Development of a sensitive chromophoric probe of P i release allowed the rate of release from actomyosin to be measured directly. White et al (1997) found that P i release from actomyosin in solution is only 75 s À1 , not sufficiently faster than the ATP hydrolysis step to support the assumption of a rapid equilibrium described above. More complex schemes could, of course, be invoked, and integration of pressure-and temperature-jump and fibre transient data led Ranatunga (1999) to postulate yet another state in this part of the actomyosin cycle.…”
Section: Details Of the Link Between Phosphatementioning
confidence: 70%
See 1 more Smart Citation
“…DOUBTS ABOUT SCHEME 1 Development of a sensitive chromophoric probe of P i release allowed the rate of release from actomyosin to be measured directly. White et al (1997) found that P i release from actomyosin in solution is only 75 s À1 , not sufficiently faster than the ATP hydrolysis step to support the assumption of a rapid equilibrium described above. More complex schemes could, of course, be invoked, and integration of pressure-and temperature-jump and fibre transient data led Ranatunga (1999) to postulate yet another state in this part of the actomyosin cycle.…”
Section: Details Of the Link Between Phosphatementioning
confidence: 70%
“…A structural change, such as tilting of the myosin head, accompanying release of the hydrolysis products from AMÁADPÁP i , causes the thick and thin filaments to slide. The order of dissociation from MÁADPÁP i is first orthophosphate (P i ), then ADP (Trentham et al 1972), and the same order applies to product release from AMÁADPÁP i in solution (White et al 1997) and in muscle fibres (Dantzig & Goldman 1985). In solution experiments with the isolated proteins, the product release steps liberate more than half of the free energy available from the net ATPase reaction, and most of this free energy change corresponds to P i release (White & Taylor 1976;Siemankowski et al 1985).…”
Section: Hints From Biochemistrymentioning
confidence: 99%
“…For example, phosphate release from activated Acanthamoeba myosin-Ic = 24 s -1 (26), myosin-V > 100 s -1 (22,33), and skeletal muscle myosin-II = 75 s -1 (24). It is not clear why myo1b evolved to have a slow rate of phosphate release, but it is likely that the motor is kinetically tuned to optimally sense tension allowing for force-dependent changes in its duty ratio (see below).…”
Section: Phosphate Releasementioning
confidence: 99%
“…This mantATP-induced dissociation is ∼ 2-fold slower than ATP-induced dissociation as measured by pyrene-actin fluorescence (1.5 ± 0.081 μM -1 s -1 ; Table 1). Fluorescently-labeled phosphate-binding protein (P i BP) was used to measure directly the rate of phosphate release (k +4 ′) in sequential-mix, single-turnover, stopped-flow experiments (11,22,24,26). Myo1b IQ was mixed with ATP, aged 7 s to allow for ATP binding and hydrolysis, and mixed with actin ( Figure 6).…”
mentioning
confidence: 99%
“…The first-order rate of actin dissociation from AM⅐T at 25°C is Ͼ5,000 s Ϫ1 (7), which is probably significantly faster than the competing repriming step (AMo⅐T 3 AMc⅐T). The latter rate has not been measured but the rate of the equivalent step in the absence of actin is Ϸ300 s Ϫ1 (23,25) and the overall rate of the composite hydrolysis step (i.e., open to closed and hydrolysis itself) is slowed by the binding of actin (26,27). The rate (AMo⅐T 3 AMc⅐T) is probably no more than 300 s Ϫ1 , which would lead to the pathway of dissociation before repriming being greatly favored.…”
Section: Discussionmentioning
confidence: 99%